Robbie Haynes: capstone - Haynes, Robbie, artist (Colorado State University. Libraries, 2022)
The artist's statement: As a designer my goal is to use my own knowledge and creative liberty to express the use of color, text, shapes & illustration in an innovative way that indulges the client's needs. I view graphic design as an opportunity to explore methods of combining my illustrative style into a professional and modern aesthetic that challenges design trends. I love designing logos, book covers, & illustrative campaigns. However, I am capable of challenging myself outside those lines to work with anyone to try and materialize their vision. I have a design process that includes various steps to insure I please my clients, and includes: Planning and sketching out any ideas and visions I have for a specific design, Digitalizing it to see how it translates on a computer, Asking peers and colleagues for any feedback and suggestions, Resolving and finalizing it until the needs and wants are satisfied with the client. Every project is a collaboration in my eyes; I want to hear the client’s feedback and suggestions on my ideas every step of the way and thrive to have a discussion on how I can create a design that satisfies their needs. Design is my passion, I am designing the life I want to live through this passion and my purpose is to create kiss ass designs that go outside the normal trends of graphic design.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design